The Privileging of English Language Use in Academia: Critical Reflections from an International Doctoral Seminar - Woodend, Jon; Fedoruk, Lisa; Beek, Avis; Roy, Sylvie; Xu, Xuequin; Groen, Janet; Li, Xiang (Emerging Trends in Education, 2019)
In this article, we, a Canadian team of doctoral researchers, reflected on our journey during an International Doctoral Research Seminar held in Beijing in 2015. As five doctoral students and two academics, we met with our doctoral colleagues from academic institutions in Brisbane (Australia) and Beijing (China). Although we did not discuss or negotiate which language we would be using in China, we were confronted with our assumption that English would be used, and that some the participants had a lower level of English competency than expected. It was apparent that this assumption of English language use privileged some (i.e., Canadian and Australian teams) while disadvantaging others (i.e., Chinese team). This confrontation brought up questions and concerns about equity in participation. As a result, this article chronicles the Canadian team reflecting on the International Doctoral Research Seminar including our privilege of using English, and coming to the position of wanting to create a more inclusive space for all participants to engage equitably in this international collaboration. As such, our reflections in this article focused on the domination of English as a lingua franca in academic spaces, in addition to how we decided to facilitate a transcultural space for all participants to be included.